Antibody‐Functionalized Magnetic Polymersomes: In vivo Targeting and Imaging of Bone Metastases using High Resolution MRI. Issue 11 (19th April 2013) - Pourtau, Line; Oliveira, Hugo; Thevenot, Julie; Wan, Yali; Brisson, Alain R.; Sandre, Olivier; Miraux, Sylvain; Thiaudiere, Eric; Lecommandoux, Sébastien
<x xml:space="preserve">Abstract</x> Multifunctional polymersomes loaded with maghemite nanoparticles and grafted with an antibody, directed against human endothelial receptor 2, are developed as novel MRI contrast agents for bone metastasis imaging. Upon administration in mice bearing bone tumor grown from human breast cancer cells, MR images show targeting and enhanced retention of antibody‐labeled polymersomes at the tumor site. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>